Prospek Pengembangan Usahatani Kakao di Desa Pangsan, Kecamatan Petang, Kabupaten Badung - RISTA ULVIA RAMADHANI; I WAYAN BUDIASA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Prospect of Cocoa Farming Development in Pangsan Village, Petang Sub-District of Badung Regency Cocoa plays an important role for the national economy, especially openingemployment opportunities, sources of income, and foreign exchange. The objectivesof this research are: to investigate the suitability of land for cocoa farming inPangsan Village, financial feasibility of cocoa farming in Pangsan Village, seen frominvestment criteria, and market prospect of cocoa commodity of Pangsan Villageproduction. The analysis used in this research is investment criteria method includingNPV, IRR, and Net B/C for financial feasibility analysis, while land suitability andmarket prospect are analyzed descriptively and qualitatively. The findings of thestudy showed that : land in Pangsan Village is appropriate (S2) for cocoa farmingand it has low productivity compared to cocoa productivity in Bali and Indonesia,cocoa farming in Pangsan village which is intercropped with coconut and bananatrees is financially feasible to be cultivated, with NPV of Rp 29.454.914,86, IRR of38%, and Net Benefit Cost Ratio (Net B/C) of 7,68, and the market prospect of cocoaproducts in Pangsan Village is not prospective for foodstuff, because the product ofcocoa produced is not fermented and not certified.